ETIKA KOMUNIKASI PEMIMPIN PERSPEKTIF HADITS - Rofiq Hidayat (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2019)
In this paper, the author presents a study of the ethics of leader communication based on the behavior of the Prophet through the hadith. This research method uses descriptive qualitative by collecting the hadiths in the kutubut tis’ah. Based on the types of communication, the traditions related to the ethics of communication verbally and nonverbally will be examined. From the results of the study, there are three hadiths that discuss the ethics of verbal communication, namely first, not too fast, clear, firm, secondly repeat until understanding, third, only speak necessary, begin and end with basmalah, and not insulting and hadith which discusses four the thing in non-verbal communication is the hadith regarding body language, signs, deeds, and objects.